Directors' remuneration and firm performance : Malaysian evidence / Salleh Hassan, Theo Christopher and Robert Evans - Hassan, Salleh; Theo, Christopher (Faculty of Accountancy & Accounting Research Institute (ARI), 2003)
The issue of board of directors' remuneration, a subset of senior management compensation, has been a matter of continuing debate and examination primarily in Western economies. However, since on the onset of the 1997 Asian financial crisis, the issue of directors' remuneration has caught the attention of corporate stakeholders of the crisis-affected economies. The objective of the present study is to explore the relationship between Malaysian directors' remuneration and firm performance. The current study proposes that the relationship between directors' remuneration and firm performance will be a positive one. However, this relationship is argued to be a weak one because of the prevailing corporate governance structures in Malaysia, which are different from that of the Western economies. This argument implicitly implies that the normal agency and efficient contracting predictions are not applicable to the extent that generally directors of Malaysian listed companies would be indifferent towards the matter. From a sample of 100 listed companies throughout the period from 1996 to 1998, it has been found that there has been positive but weak relationship between current year directors' remuneration and current year internal growth measures and financial performance indicators. Further, the evidence shows an even weaker relationship between directors' remuneration and financial performance than that between directors' remuneration and internal growth measures for all the 3 years from 1996 to 1998. From the lag-effect analysis, the conclusion is consistent with the current year analysis. However, the strength of the relationship reported by the lag-effect analysis is generally stronger than that reported using the current year analysis.